2018
DOI: 10.1038/s41598-018-25452-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5-aminolevulinic acid supplementation on home-based walking training achievement in middle-aged depressive women: randomized, double-blind, crossover pilot study

Abstract: Depressive patients often experience difficulty in performing exercise due to physical and psychological barriers. We examined the effects of 5-aminolevulinic acid (ALA) with sodium ferrous citrate (SFC) supplementation during home-based walking training in middle-aged depressive women. Nine outpatients [53 ± 8 (SD) yr] with major depressive disorder participated in the pilot study with randomized, placebo-controlled, double-blind crossover design. They underwent two trials for 7 days, each performing interval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Some of the top ranked non-traditional treatments for depression were of interest because prior work had suggested them as possible antidepressants. For example, D-serine (second highest for females) 52 , curcumin 53 , creatine 54 , elevated temperature 55 , albiflorin 56,57 , alpha and gamma tocopherol with vitamin E 58 , nicotinamide riboside 59 , aminolevulinic acid 60 , celastrol 61 , and zinc 62 each have been evaluated in some context as a possible treatment for depression. The datasets for D-serine included an unusually high ratio of upregulated relative to downregulated genes overall 63 , though, so additional caution may be needed when interpreting that result.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the top ranked non-traditional treatments for depression were of interest because prior work had suggested them as possible antidepressants. For example, D-serine (second highest for females) 52 , curcumin 53 , creatine 54 , elevated temperature 55 , albiflorin 56,57 , alpha and gamma tocopherol with vitamin E 58 , nicotinamide riboside 59 , aminolevulinic acid 60 , celastrol 61 , and zinc 62 each have been evaluated in some context as a possible treatment for depression. The datasets for D-serine included an unusually high ratio of upregulated relative to downregulated genes overall 63 , though, so additional caution may be needed when interpreting that result.…”
Section: Discussionmentioning
confidence: 99%
“…5‐Aminolevulinic acid supplementation in mice enhances Complex IV (cytochrome c oxidase, COX) activity and ATP production levels, and combined treatment with 5‐ALA and SFC was reported to upregulate the expression of electron transfer chain complexes III, IV, and V in the white adipose tissue of obese mice 10 . These study results suggest the possibility of a definitive therapy against mitochondrial disease by an “enzyme reinforcing treatment” that reinforces the activity of remaining mitochondrial respiratory chain enzymes to improve the mitochondrial function 11,12 …”
Section: Introductionmentioning
confidence: 80%
“…Previous study has suggested that 6 weeks 5-ALA administration improved sleep quality in subjects with insomnia or difficulty sleeping, reducing the Pittsburgh Insomnia Rating Scale-20 Question (PIRS-20) 22 . In addition, 5-ALA improved exercise efficiency and home-based walking training achievement in older women 23 , and also improved depressive symptoms www.nature.com/scientificreports/ measured by the Montgomery-Åsberg Depression Rating Scale (MADRS) in middle-aged depressive women 24 . These evidences are consistent with our results that 5-ALA improves physical tiredness and negative mood.…”
Section: Discussionmentioning
confidence: 98%